2021
DOI: 10.3389/fimmu.2021.569287
|View full text |Cite
|
Sign up to set email alerts
|

Autoreactive Peripheral Blood T Helper Cell Responses in Bullous Pemphigoid and Elderly Patients With Pruritic Disorders

Abstract: Bullous pemphigoid (BP) is a prototypic autoimmune disorder of the elderly, characterized by serum IgG autoantibodies, namely anti-BP180 and anti-BP230, directed against components of the basal membrane zone that lead to sub-epidermal loss of adhesion. Pruritus may be indicative of a pre-clinical stage of BP, since a subset of these patients shows serum IgG autoantibodies against BP230 and/or BP180 while chronic pruritus is increasingly common in the elderly population and is associated with a variety of derma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 64 publications
0
15
0
2
Order By: Relevance
“…In this latter report, the authors also showed that some elderly patients with pruritus have autoreactive T-cells directed against the N- and C-domains of BP180. These autoreactive T-cells exhibited a cytokine profile similar to that typically observed in BP patients [ 82 ]. IgE antibodies against BP230, and to a lesser extent BP180, have also been found in pruritic elderly patients [ 83 ].…”
Section: Bp230 Autoantibodies In Pruritus Of the Elderlymentioning
confidence: 85%
“…In this latter report, the authors also showed that some elderly patients with pruritus have autoreactive T-cells directed against the N- and C-domains of BP180. These autoreactive T-cells exhibited a cytokine profile similar to that typically observed in BP patients [ 82 ]. IgE antibodies against BP230, and to a lesser extent BP180, have also been found in pruritic elderly patients [ 83 ].…”
Section: Bp230 Autoantibodies In Pruritus Of the Elderlymentioning
confidence: 85%
“…[114][115][116] In addition, Th17 cells and autoreactive Th1/Th2 cells have been observed including a mixed spectrum of cytokines, such as IL-17, IFNγ, and IL-5. 117 Moreover, Th2 cytokines were found in blisters, which point to an additional role of Th2 cells, a fact that is further substantiated by the identification of anti-BP180/230 IgE autoantibodies. 118,119 Alopecia areata is a chronic, relapsing, skin disease leading to patchy hair loss that can reversibly affect small areas of the scalp or trunk, but can also progress to large, therapy resistant areas with complete hair loss.…”
Section: Other Inflammatory Skin Diseasesmentioning
confidence: 86%
“…Autoreactive IgG or IgE autoantibodies to the antigens BP180 or BP230 induce pruritic eczematous or urticarial lesions and subepidermal blister formation, mainly in elderly patients 114–116 . In addition, Th17 cells and autoreactive Th1/Th2 cells have been observed including a mixed spectrum of cytokines, such as IL‐17, IFN‐γ, and IL‐5 117 . Moreover, Th2 cytokines were found in blisters, which point to an additional role of Th2 cells, a fact that is further substantiated by the identification of anti‐BP180/230 IgE autoantibodies 118,119 …”
Section: The Role Of T Cells In Inflammatory Skin Diseases Including ...mentioning
confidence: 99%
“…Analysis of T lymphocyte proliferative responses to antigenic or mitogenic stimuli is a vital parameter used in both diagnosis and monitoring of a variety of immune responses. Most commonly applied techniques are based on the incorporation of tritiated thymidine ( 3 H-TdR) or enzyme-linked immunospot (ELISPOT) analysis ( 13 , 14 ). Both rely on a rather long ex vivo expansion periods and stimulation protocols (up to 11 days).…”
Section: Introductionmentioning
confidence: 99%